Declarative agent languages and technologies X : 10th International Workshop, DALT 2012, Valencia, Spain, June 4, 2012, Revised Selected Papers - Dennis, Louise; Mascardi, Viviana; Vasconcelos, Wamberto; Baldoni, Matteo (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-proceedings of the 10th International Workshop on Declarative Agent Languages and Technologies, DALT 2012, held in conjunction with the 11th International Joint Conference on Autonomous Agents and Multiagent Systems (AAMAS 2012) at Valencia, Spain, in June 2012.   The volume contains 13 revised selected presented at DALT 2012.The papers cover the following topics:  declarative languages and technologies, computational logics, declarative approaches to engineering agent-based systems, models of business interactions among agents, and models of trust, commitments, and reputation for agents.